PENGARUH SOSIALISASI, SANKSI DAN PERSEPSI AKUNTABILITAS TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR - Widnyani, Ida Ayu Dewi; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2016)
This research aimed to get empirical evidence about the influence of socialization of taxation, tax penalties and perceptions the accountability of public services on tax compliance in paying motor vehicle tax in License Bureau Tabanan. The theory used is the theory of planned behavior. The population in this research are all compulsory motor vehicle tax in the Office of the SAMSAT Tabanan City. The samples used of 100 respondents was calculated based on the formula slovin of sampling accsidental. The data collection by survey method through questionnaire . The data analysis technique used in this research is multiple linear regression. Based on the analysis shows that socialization of taxation, tax penalties and perceptions the accountability of public services positive effect on tax compliance in paying motor vehicle tax in the Office of the SAMSAT Tabanan City.
Keywords: tax compliance; socialization; tax penalties; accountability of public services